Rapid Reperfusion Therapy in Acute Ischemic Stroke Reduces Complications and Improves Outcomes - Dowell, Masha (MD Conference Express, 2014)
The American Heart Association (AHA)/American Stroke Association (ASA) guidelines recommend a door-to-needle (DTN) time of =60 minutes for reperfusion therapy for acute ischemic stroke patients [Jauch EC et al. Stroke 2013]. The rapid treatment is important for improving stroke outcome, but many studies have concluded that this time frame has been met by <30% of intravenous tissue plasminogen activator (t-PA)-treated stroke patients. This article discusses the principal results from the Target: Stroke Initiative, a national program organized by the AHA/ASA, which addresses this timing dilemma by increasing the proportion of stroke patients with DTN time frames of <60 minutes.